If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -69 = -21 + -6x Solving -69 = -21 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -69 + 6x = -21 + -6x + 6x Combine like terms: -6x + 6x = 0 -69 + 6x = -21 + 0 -69 + 6x = -21 Add '69' to each side of the equation. -69 + 69 + 6x = -21 + 69 Combine like terms: -69 + 69 = 0 0 + 6x = -21 + 69 6x = -21 + 69 Combine like terms: -21 + 69 = 48 6x = 48 Divide each side by '6'. x = 8 Simplifying x = 8
| .750s-.5=.25s+5 | | 15y^2+10y=34 | | 7x-6-2x=9x-5 | | -2p+2=14 | | -6(v+4)+3v+6=8v+12 | | 3-3z=12 | | (-9x)(-2y)=0 | | 3y+2(y-8)=6y-3(y-10) | | -3(-4x+4)=72 | | -5(2t-3)+2t=4t-8 | | 5(4+x)=19 | | f-8f=20-12f | | 5x-3x+x-4+4x= | | -161=7(5x+2) | | 8b+2=15b-12 | | -98=2(-1+6k) | | 24x-7=10 | | 3(-6gf-4)= | | 84=3(4x-4) | | 0.5m=-15 | | 40=1/210h | | 3.4=-13.4+(-3.4x)+1.7x | | 6x=x+3 | | 3n+3n=18 | | 2(x+75)=219 | | 4(d)-3=28 | | (8)x=16 | | 5x+9=3x+25 | | 0.24=1n(y) | | m+6-5m=10 | | 5(n+6)+25=9 | | 1=14(8t+4) |